Path planning for autonomous navigation in roundabouts using an improved triangular based polynomial estimation technique for bezier curve generation with aa and aa* algorithms - Sajith Akhil, Vinayak (2023)
Autonomous vehicle (AVs) development is a rapidly growing research field. The AVs need to inspect the environment and detect the obstacle to create a path according to the environment. Path planning is a critical stage in the operation of vehicles, wherein the path is generated based on the surrounding environment to ensure safe and efficient navigation. The path is created for the vehicle to travel through different intersections. Among that roundabout is a type of intersection where path planning is challenging due to their complex shape and different traffic rules. To overcome this, different curve fitting methods were used to create path. However, the commonly used method is Bezier curve based curve fitting method which depends on the position of the control points. Many researchers have established different methods to position the control points but the change in the shape of roundabout cause the path to be inaccurate as the position of the control points are fixed. Therefore, the objective of the research is to introduce an enhanced method for calculating the control points for Bezier curve generation according to the shape of the roundabout. A triangular-based polynomial estimation technique is introduced, which helps calculate the Bezier curve's control points based on the points selected in the path. An equation is introduced which helps in calculating the control points based on the points selected and the respective segmentation factor (